Teacher Burnout Prevention Strategies in Indonesia Through Wellbeing Pedagogy Based on Islamic Educational Values - Farhana Rodhiyah; Ayu Anzila Munawwaroh; Vicky Nunaini Yogri Pratiwi; Ahmad Hanif; Thoriq Aziz Asrinsyirah; Husnul Khotimah (Edudeena : Journal of Islamic Religious Education, 2025)
Teacher burnout has become an urgent issue in Indonesian education, characterized by rising emotional exhaustion, administrative pressure, and increasingly complex curriculum demands. Although many studies highlight the causes of burnout, there remains a gap regarding integrated prevention strategies that align with Indonesia’s cultural context. This study aims to describe the burnout conditions experienced by teachers and analyze the application of wellbeing pedagogy based Islamic education value as a preventive strategy that is consistent with the social, spiritual, and communal values embedded in Indonesian education. The research employed a literature study with a qualitative approach through content analysis and thematic analysis of relevant primary and secondary sources. The findings indicate that teacher burnout is influenced by excessive workloads, limited organizational support, and weak emotional regulation and social support systems. Wellbeing pedagogy offers a comprehensive approach by strengthening emotional competencies, fostering positive school culture, promoting mindfulness, and encouraging collaborative social support. In conclusion, integrating wellbeing pedagogy has strong potential to serve as an effective and sustainable strategy for preventing teacher burnout. It also provides important implications for developing more humane and wellbeing-oriented educational policies and practices.